Molybdenum Sheet Metal Test Device - Bastovansky, Ronald; Tropp, Michal; Lukac, Michal; Brumercik, Frantisek (Communications - Scientific letters of the University of Zilina, 2017)
The paper presents the construction of a device that allows processing the Baosteel/Sanchez experiment. The experiment simulates the brake ribs by deep drawing of the molybdenum sheet metal.